Challenging Pax Americana: The Commercial Imperative in Chinese Arms Exports to Africa - A Case Study of Uganda and Kenya - Elijah Munyi (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
The past decade has seen a rise in the global share of Chinese defense sales – in this publication, Elijah N. Munyi looks at the implications for the African continent. Munyi examines the motivations for some African states' growing preference for Chinese arms with a particular focus on case studies conducted in Uganda and Kenya. Read on to find out how Prof. Munyi delves into the nuance behind the preferences for military procurement.
Keywords: 330